A comparative simulation study of the effect of column suppression on shear stress in an L-shaped RC wall with openings - Salem, Merabti (Brazilian Journal of Production Engineering, 2025)
Buildings require the use of reinforced concrete shear walls to ensure their stability and seismic resistance. Among the effective configurations, L-shaped reinforced concrete (RC) walls placed at the corners of buildings perfectly meet the seismic resistance criteria. In this study, a new approach was explored, consisting of removing the columns from the L-shaped walls, and its results were compared to those of walls with columns. To evaluate this configuration, numerical simulations were performed on buildings located in a high-seismicity area. The main parameters considered included the thickness of the shear walls, the percentage of openings, and the number of stories. The simulation results reveal that removing columns from L-shaped shear walls with openings leads to maximum shear stress reduction, regardless of wall thickness or number of stories. The study confirms the beneficial effect of column removal for openings below 25%, while retaining columns proves advantageous for larger openings.
Keywords: High seismicity; Buildings; L-shaped RC; Columns; Numerical analysis; Shear stress; Openings